IMPLEMENTASI DIGITAL MARKETING TERHADAP PENINGKATAN PENJUALAN BAKSO HOME INDUSTRI DESA KEDAUNG KECAMATAN SAWANGAN KOTA DEPOK - Abdurohman, Dede (Indonesian Journal of Economy, Business, Entrepreneuship and Finance, 2025)
The rapid development of information technology has an impact on society in supporting various business activities, both large and small, so that they can be recognized globally. The most obvious impact is that apart from being known, it can also increase sales volume and profits. By using digital marketing, in this case social media, Meatball Traders from Kedaung Village, Depok City market home industry products in the form of small shop or home-made meatballs. Initially this activity was only used to fill free time, but now it has become the main activity to increase economic turnover in the household. In the past, the sales activities of this industrial product were conventional and traditional, they made products only based on orders. However, after getting to know about social media, some of the residents of Kedaung have started to receive lots of orders, so the sales volume has increased rapidly compared to when selling using the old method. Digital marketing is seen as the best media as the most effective and efficient means of promotion and is able to increase sales volume significantly.